Informal Competition in Kazakhstan - Sarsenbayeva, Aigerim (Nazarbayev University School of Sciences and Humanities, 2017)
The size of the informal economy in Kazakhstan declined from 42.6% in 1999 to 33.8% in 2015. The informal economy can make an important contribution to solving the problem of fiscal deficit without forgoing economic growth and employment. In my thesis, I am evaluating the effect of competition stemming from informal firms on the of formal enterprises. I conduct fixed and changing structure analysis to understand the underlying factors behind the decline in the informal sector competition in Kazakhstan. In my research I use European Bank for Reconstruction and Development’s Business Environment and Enterprise Performance (BEEPs) 2008-2009 and 2012-2013 surveys. This is the period that covers financial crisis and enables the study of the structure of the informal competition faced by registered firms at the micro level. The present study utilises firm-specific variables, industry specific variables and business environment. For corruption and taxes I use industry averages to address the issue of endogeneity. My findings suggest that more than 90% of the decline in the informal competition can be attributed to the socio economic changes. Focusing on the observed heterogeneity the main contributors to the decline in the rate of the informal competition are due to an educated workforce, access to finance, losses due to theft, transportation as an obstacle to current operations and the services sector. The changes in firm size, taxes and labour regulations have kept competition from decreasing even further.
Keywords: Informal Economy; Competition Against Informal Firms; Kazakhstan